Successful Treatment of Severe Post-craniotomy Meningitis Caused by an Escherichia coli Sequence Type 410 Strain Coharboring blaNDM–5 and blaCTX–M–65 - Yang, Qing; Zhang, Piao-piao; Jiang, Yan; Zheng, Xiu-jue; Zheng, Min; Qu, Ting-ting (Frontiers in Microbiology, 2021)
Intracranial infections caused by multidrug-resistant Gram-negative bacterium have led to considerable mortality due to extremely limited treatment options. Herein, we firstly reported a clinical carbapenem-resistant Escherichia coli isolate coharboring blaNDM-5 and blaCTX-M-65 from a patient with post-craniotomy meningitis. The carbapenem-resistant Escherichia coli strain CNEC001 belonging to Sequence Type 410 was only susceptible to amikacin and tigecycline, both of which have poor penetration through the blood-brain barrier (BBB). The blaCTX-M-65 gene was expressed on a 135,794 bp IncY plasmid. The blaNDM-5 gene was located on a genomic island region of an IncX3-type plasmid pNDM5-CNEC001. Based on the characteristics of the strain, we presented the successful treatment protocol of intravenous (IV) tigecycline and amikacin combined with intrathecal (ITH) amikacin in this study. Intracranial infection caused by Escherichia coli coharboring blaNDM-5 and blaCTX-M-65 is rare and fatal. Continuous surveillance and infection control measures for such strain need critical attention in clinical settings.